Rothwell's augmented generations of innovation theory: Novel theoretical insights and a proposed research agenda - Chris W. Callaghan (South African Journal of Business Management, 2019)
Background: Technological advances necessitate the reconceptualisation of certain seminal theory. Novel developments in Internet and Communication Technologies have disrupted certain markets, industries and processes.Objectives: Rothwell's seminal generations of innovation typology provides a categorisation of advances in innovation theory. In so doing, it provides an overarching logic that relates these advances to a production function, categorising the way each wave of innovation theory has driven the time/cost curve closer to its axis. The objective of this article is to augment this typology to include theory that relates to novel technological advances, with implications for the innovation time/cost curve.Method: As a conceptual article, this work seeks to offer a synthesis of theory, extending Rothwell's schema to incorporate theory related to novel technological developments.Results: Lacking in Rothwell's conceptualisation of five generations of innovation is consideration of recent technological advances which necessitate a reformulation of this schema to take into account new scale relationships made possible by recent technological developments. This article seeks to extend Rothwell's theoretical framework to incorporate these new potentialities.Conclusion: In augmenting Rothwell's theoretical schema, certain implications for society and industries are predicted, and suggestions are made for a proposed research agenda.
Keywords: 650